Odpowiedzi

2009-11-19T22:16:47+01:00
A= <-10;-2> , B= (-∞; 0), C= <-4; 5)


a.)
C u A = <-10; 5)
B \ (C u A) = (-∞; -10)


b.)
B n C = <-4; 0)
(B n C) \ A = (-2; 0)


c.)
C \ B = <0; 5)
R \ (C\ B) = (-∞; 0) u <5; +∞)
2009-11-19T22:20:26+01:00
A) =(- nieskonczonosc;-10)
b) =(- nieskonczonosc;-10)U(-2;5)
c)=(- nieskonczonosc;0)U(5;+nieskończoność)
2009-11-19T22:34:07+01:00
A.) B\ (С υ A)
(С υ A) = <-10;5)
B\ (С υ A) = (-∞;-10)


b.) (B П C) \ A
(B П C) = <-4;0)
(B П C) \ A = zbiór pusty


c.) R \ (C\ B)
(C\ B) = <0;5)
R \ (C\ B) = (-∞;0) υ <5;∞)